ANTARA LELAH DAN DUKUNGAN: BAGAIMANA ACADEMIC BURNOUT DAN FAMILY SUPPORT MEMPENGARUHI PROKRASTINASI AKADEMI MAHASISWA - Iin Yulianti; Erni Zuliana; Novi Sundari (Guidance and counseling the university of Prof. Dr. Hazairin. SH, 2026)
Academic procrastination is a common problem faced by many students, including universitystudents. This study was motivated by the phenomenon of academic procrastination among universitystudents, which is presumed to be influenced by internal factors such as academic burnout andexternal factors such as family support. The purpose of this study was to examine the relationshipbetween academic burnout and family support with academic procrastination among universitystudents.This study employed a quantitative approach using multiple regression analysis. Thesampling technique used was purposive sampling, involving 67 university students in Indonesia asparticipants. Data were collected using three instruments: the Academic Procrastination Scale, theAcademic Burnout Scale, and the Family Support Scale. Data analysis was conducted using JASPfor Windows version 0.19.1.0.The results revealed a significant simultaneous relationship betweenacademic burnout and family support with academic procrastination (R = 0.366; F = 4.953; p <0.05), with an effective contribution of 13.6%. Partially, there was no significant positiverelationship between academic burnout and academic procrastination (effective contribution =3.9%). In contrast, a significant negative relationship was found between family support andacademic procrastination (effective contribution = 9.7%).The findings indicate that family supportplays a more dominant role in reducing academic procrastination among university studentscompared to academic burnout.